Educational Serious Games as a Service: Challenges and Solutions - Sandí Delgado, Juan Carlos (2019)
Cloud computing is a distributed computing technology that facilitates access to the resources in a dynamic, scalable and highly available manner. One of its service models is SaaS (Software as a Service) which allows executing Web applications in a flexible and elastic way while offering collaborative characteristics. The integration of SaaS in educational environments promotes academic performance and facilitates knowledge management, allowing for storage, exchange, access and synchronization of information. On the other hand, educational serious games promote among the people involved: collaboration, communication, social abilities, critical thinking and problem solving. The main objective of this investigation is to analyze the challenges that SaaS, with its collaborative and multitenancy characteristics present to the execution of educational serious games. This is named ESGaaS - Educational Serious Games as a Service. The analysis was developed based on a review of the existing literature through the methodology known as Systematic Mapping Studies (SMS) which facilitated the generation of investigation questions, search strategies, key words and inclusion and exclusion criteria applied to identify articles in several sources. This investigation facilitated the development of a list of functional characteristics that the educational serious games will acquire when used as software for service.